Penerapan Pemahaman Hadits-Hadits Pendek Dalam Membentuk Prososial Anak Di RA-B Al-Mardiyah Waru Pamekasan - Nurul Khalifatul Jannah; Eva Rosita (STAI Publisistik Thawalib Jakarta, 2022)
The application of understanding short hadiths in shaping the prosocial behavior of children at RA-B Al-Mardiyah needs to be developed in accordance with the behavior exemplified by the Prophet. . So the researchers took the initiative to conduct research at the institution with the aim of knowing the application of understanding short hadiths in shaping children's prosocial behavior and to find out the forms of children's prosocial behavior in RA-B Al- Mardiyah. The approach used in this research is qualitative with the type of case study research. While the data collection using observation, interviews, and documentation. The analysis used is data reduction techniques, data presentation, and conclusions. The results of the study indicate that (1) the method used by teachers at RA-B Al- Mardiyah through the 6M method, namely, reciting words, repeating readings, alternating reading between teachers and students, reciting together, moving both hands and sing with joy. (2) Forms of children's prosocial behavior include helping behavior, sharing, working together, donating, being honest, generous and prioritizing the rights and welfare of others.